Understanding digital competence profiles among in-service and prospective art teachers in Kazakhstan - Masoumeh Shiri; Aidar Kuzdeubayev; Aidyn Kozhagulov; Zhazira Stambekova; Rakhat Berikbol; Nurgul Koshkinbayeva (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study investigates digital competence profiles between in-service art teachers and prospective art teachers (students in art teacher education programs) across three universities in Kazakhstan. Addressing a notable gap in understanding how digital skills are distributed in art education, the research employs a comparative descriptive design with a mixed-methods approach, combining a structured survey based on the European DigCompEdu framework and semi-structured interviews. Teachers were measured in the six domains of digital competence: professional engagement, digital resources, teaching and learning, assessment, empowering learners and enabling learners’ digital competence. Data from 197 participants (41 teachers, 156 prospective) showed following profiles: prospective fare better in creative and communication competencies; in-service performances are good on professional engagement and structured pedagogical activities. Face-to-face interviews triangulated findings across the survey and revealed how teacher use of digital tools in teaching and learning is shaped by generational differences prior training, as well as professional experience. These results highlight a necessity to develop role-sensitive digital skills in the field of art education. By triangulating quantitative and qualitative evidence, the study provides a nuanced understanding of digital competence across career stages and supports targeted training initiatives. It also lays the groundwork for future research using performance-based assessments and broader comparative contexts.